ANALISIS EFEKTIVITAS PROMOSI PEMASARAN IKLAN SIAR PRODUK SUNSILK MENGGUNAKAN DIRECT RATING METHOD - Akmaludin, Akmaludin (www.bsi.ac.id, 2012)
Marketing communications are the mainstay for every manufacturer to influence consumers against products that it markets, this is done there is no other word is to improve mind share to the public in order to increase selling product. This is done because the aspect of remembrance will create awareness to the end consumer purchases would take action to a product recall. A1arketing promotions are often used manufacturers to introduce their products to market is the advertising, ad vertising has a very poweiful force to inf orm, communicate, and even affect the consumer to the product marketing, media fisheries have a very long way to reach consumers is media such as radio and television broadcasting . Advertising products that are advertised through the medium of television broadcasting, the level of effectiveness can be analyzed by using certain methods. One method used to measure the effectiveness of advertising is Direct Rating Method (DRM). Analysis of broadcast product advertising that will measure its iffectiveness is product Sunsilk version